2012
DOI: 10.1188/13.onf.44-52
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Preferences Among a Population-Based Sample of Colorectal Cancer Survivors

Abstract: Consumer physical activity tracking devices (PATs) have gained popularity to support individuals to be more active and less sedentary throughout the day. Wearable PATs provide real-time feedback of various fitness-related metrics such as tracking steps, sedentary time, and distance walked. The purpose of this study was to examine the prevalence and correlates of PAT ownership and use among a population-based sample of adults. A representative sample of adults !18 years (N = 1,215) from Alberta, Canada were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 23 publications
0
42
1
Order By: Relevance
“…A study of long term CRC survivors [22] reported a response rate of 51%, and one among rectal cancer reported a response rate of 61% [21]. Others had lower response rates than ours; 34% among a random sample of Canadian CRC survivors [18] and 47% in a US study [19] that reported lower response rates among those who were older, non-white or diagnosed with metastatic cancer. Maxwell et al [20] achieved a 33% overall response rate among 3,316 CRC cases in Los Angeles and tested differences between incentives, compensation for completing the survey, first class mail versus registered mail and did not see significant differences in any combination of these factors.…”
Section: Discussionmentioning
confidence: 71%
“…A study of long term CRC survivors [22] reported a response rate of 51%, and one among rectal cancer reported a response rate of 61% [21]. Others had lower response rates than ours; 34% among a random sample of Canadian CRC survivors [18] and 47% in a US study [19] that reported lower response rates among those who were older, non-white or diagnosed with metastatic cancer. Maxwell et al [20] achieved a 33% overall response rate among 3,316 CRC cases in Los Angeles and tested differences between incentives, compensation for completing the survey, first class mail versus registered mail and did not see significant differences in any combination of these factors.…”
Section: Discussionmentioning
confidence: 71%
“…Although heavy smoking or alcohol intake among CRC survivors is infrequent, many survivors fail to meet physical activity, body mass index and fruit and vegetable intake recommendations (Chambers et al, 2012a(Chambers et al, , 2012bGrimmett et al, 2011;Hawkes et al, 2008;James et al, 2006;Johnson et al, 2009;Lynch et al, 2007aLynch et al, , 2008cMcGowan et al, 2013;Peddle et al, 2008aPeddle et al, , 2008bPullar et al, 2012;SpeedAndrews et al, 2012SpeedAndrews et al, , 2013Thraen-Borowski et al, 2013;Wijndaele et al, 2009). Achieving recommended levels of physical activity may be difficult if the survivor is experiencing chronic effects of CRC, treatment or co-morbidities (Anderson et al, 2013;Chambers et al, 2009;Hawkes et al, 2008;Lynch et al, 2007aLynch et al, , 2008cPalmer et al, 2013).…”
Section: Duality Of Positive and Negative Aspectsmentioning
confidence: 99%
“…Survivors face new challenges specific to the nature of their disease, encompassing bowel management, ostomy care, health promotion, diet and lifestyle advice, requiring significant practical and psychological support to facilitate adjustment (Anderson et al, 2013;Haggstrom et al, 2009;Ho et al, 2015;McGowan et al, 2013;McMullen et al, 2008;Nikoletti et al, 2008;Pullar et al, 2012). Other unmet information and healthcare needs were similar to those of survivors of other forms of cancer, and included information about diagnosis, investigations, treatments, prognosis, medication management, surveillance, follow-up care, genetic risk, management of chronic side-effects, return to work, financial concerns and who to contact should cancer-related problems arise (Bains et al, 2012;Baravelli et al, 2009;Esplen et al, 2007;Faul et al, 2012;Nikoletti et al, 2008;Sisler et al, 2012;Tofthagen, 2010;Vadaparampil et al, 2010).…”
Section: The Constellation Of Met and Unmet Survivorship Needsmentioning
confidence: 99%
“…The SEP intervention is based on the highly successful Diabetes Prevention Program (12) and Look AHEAD (13) studies with modifications and enhancements for colon cancer survivors (14)(15)(16). The key components of the SEP intervention include: (i) clear and challenging exercise goals, (ii) some supervised exercise sessions, (iii) free or low-cost access to a fitness facility, (iv) frequent and ongoing contacts including some face-to-face sessions with qualified staff, (v) individual tailoring of the intervention, (vi) written materials, and (vii) the application of behavior modification techniques based on a validated theoretical model.…”
Section: Interventionsmentioning
confidence: 99%